Leisure Physical Activity and the Risk of Fracture in Men - Michaëlsson, Karl (Public Library of Science, 2007)
BACKGROUND: Data from previous studies are inconsistent, and it is therefore uncertain whether, to what extent, and at what level leisure physical activity influences the risk of osteoporotic fractures in men. METHODS AND FINDINGS: A cohort of 2,205 men, 49–51 y of age, was enrolled in a longitudinal, population-based study. Leisure physical activity and other lifestyle habits were established at baseline and at ages 60, 70, 77, and 82 y. During 35 y of follow-up, 482 men had at least one fracture. Cox's proportional hazards regression was used to determine hazard ratios (HRs) of fracture associated with time-dependent physical activity habits and covariates. Men with a sedentary lifestyle (HR 2.56, 95% confidence interval 1.55–4.24) or men who walked or bicycled only for pleasure (HR 1.61, 95% confidence interval 1.10–2.36) had an increased adjusted risk of hip fracture compared with men who participated in regular sports activities for at least 3 h/wk. At the end of follow-up, 8.4% of the men with a high physical activity, 13.3% of the men with a medium physical activity, and 20.5% of the men with a low physical activity had suffered a hip fracture. According to the estimation of population-attributable risk, one third of all hip fractures could be prevented by participation in regular sports activities. High activity also conferred a reduced overall fracture risk. CONCLUSIONS: Our data indicate that regular sports activities can reduce the risk of fractures in older men.